Immobilization-Free Electrochemical Sensor Coupled with a Graphene-Oxide-Based Aptasensor for Glycated Albumin Detection - Wassa Waiwinya; Thitirat Putnin; Dechnarong Pimalai; Wireeya Chawjiraphan; Nuankanya Sathirapongsasuti; Deanpen Japrung (Biosensors, 2021)
An immobilization-free electrochemical sensor coupled with a graphene oxide (GO)-based aptasensor was developed for glycated human serum albumin (GHSA) detection. The concentration of GHSA was monitored by measuring the electrochemical response of free GO and aptamer-bound GO in the presence of glycated albumin; their currents served as the analytical signals. The electrochemical aptasensor exhibited good performance with a base-10 logarithmic scale. The calibration curve was achieved in the range of 0.01–50 µg/mL. The limit of detection (LOD) was 8.70 ng/mL. The developed method was considered a one-drop measurement process because a fabrication step and the probe-immobilization process were not required. This simple sensor offers a cost-effective, rapid, and sensitive detection method, and could be an alternative approach for determination of GHSA levels.